Otimização de tráfego em ambiente real de manufatura por meio de aceleradores WAN - Frinhani, Rafael M. D.; Serafim, Wallace F.; Batista, Bruno G. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Applications that traffic over a Wide Area Network (WAN), which can connect offices and datacenters across the globe, suffer from performance degradation caused by problems such as latency and packet loss. WAN optimization aims to minimize or eliminate the impact caused by WAN limitations to improve the performance of systems and applications. This paper seeks to analyze the acquisition of a WAN optimization solution considering technical and business aspects, by comparing tested solutions in the real environment of manufacturing multinational. Has been found that the purchase of a WAN optimization solution provides the necessary performance for business operation, besides quick return on investment.